Magnetic Resonance Imaging Staging to Evaluate the Stability of Capitellar Osteochondritis Dissecans Lesions. (August 2014) - Itsubo, Toshiro; Murakami, Narumichi; Uemura, Kazutaka; Nakamura, Koichi; Hayashi, Masanori; Uchiyama, Shigeharu; Kato, Hiroyuki
Background: Treatment for capitellar osteochondritis dissecans (COCD) lesions is usually based on their stability from the bony floor after arthroscopic or open direct observation. Thus, a noninvasive means of lesion stability assessment by use of imaging is desirable to preoperatively determine treatment strategy. Purpose: To evaluate our modified MRI staging system for COCD, we compared the results of MRI staging with the International Cartilage Repair Society (ICRS) classification for lesion stability. Intra- and interrater reliability for MRI staging was examined as well. Study Design: Cohort study (diagnosis); Level of evidence, 2. Methods: Fifty-two COCD lesions were preoperatively evaluated by T2-weighted MRI and classified into 5 stages: stage 1 = normally shaped capitellum with several spotted areas of high signal intensity that is lower than that of cartilage; stage 2 = as with stage 1 but with several spotted areas of higher intensity than that of cartilage; stage 3 = as with stage 2 but with both discontinuity and noncircularity of the chondral surface signal of the capitellum and no high signal interface apparent between the lesion and the floor; stage 4 = lesion separated by a high intensity line in comparison with cartilage; and stage 5 = capitellar lesion displaced from the floor or defect of the capitellar lesion noted. The MRI staging results were compared with the intraoperative ICRS classification for lesion stability of each patient. Sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were all determined for fragment instability. Intra- and interrater correlations for our MRI staging were calculated among 3 examiners. Results: Preoperative MRI grading correctly matched ICRS classification in 49 of 52 patients (94%), with a sensitivity of 100% and a specificity of 80%. The PPV and NPV were 93% and 100%, respectively, for diagnosing lesion instability. Intrarater reliability (intraclass correlation coefficient [ICC]) for MRI staging was high at ICC(1, 1) = 0.86 and ICC(1, 2) = 0.90, as was interrater reliability at ICC(2, 1) = 0.82 and ICC(2, 3) = 0.88. Conclusion: The MRI staging system provides accurate and reliable evidence for estimating ICRS classification and instability of COCD and is useful to decide appropriate treatment.